2017
DOI: 10.1016/j.curtheres.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dapagliflozin on Body Composition and Liver Tests in Patients with Nonalcoholic Steatohepatitis Associated with Type 2 Diabetes Mellitus: A Prospective, Open-label, Uncontrolled Study

Abstract: BackgroundNonalcoholic steatohepatitis (NASH) is an active form of nonalcoholic fatty liver disease. Risk factors for NASH include type 2 diabetes mellitus (T2DM) and obesity. Sodium–glucose cotransporter 2 (SGLT2) inhibitors used to treat T2DM prevent glucose reabsorption in the kidney and increase glucose urinary excretion. Dapagliflozin is a potent, selective SGLT2 inhibitor that reduces hyperglycemia in patients with T2DM and has been demonstrated to reduce some complications associated with NASH in rodent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
78
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 39 publications
15
78
2
5
Order By: Relevance
“…Although the drug had a mild osmotic diuretic effect, it did not increase the occurrence of electrolyte or acid‐base balance disorders. These safety and tolerability findings are consistent with those reported for canagliflozin and dapagliflozin in clinical studies conducted in the United States …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although the drug had a mild osmotic diuretic effect, it did not increase the occurrence of electrolyte or acid‐base balance disorders. These safety and tolerability findings are consistent with those reported for canagliflozin and dapagliflozin in clinical studies conducted in the United States …”
Section: Discussionsupporting
confidence: 88%
“…These safety and tolerability findings are consistent with those reported for canagliflozin and dapagliflozin in clinical studies conducted in the United States. 15,17 The PK characteristics of rongliflozin observed in participants with T2DM were similar to those observed in healthy participants, as predicted by a two-compartment model with first-order (two-stage) absorption. 18 Rapid oral absorption of rongliflozin was observed in the SAD and MAD groups.…”
Section: Discussionsupporting
confidence: 53%
“…17 In a pooled analysis in 232 Japanese patients, Seko et al also found a significant reduction in plasma ALT with canagliflozin. 18 Similar results have been reported in recent small uncontrolled studies with other SGLT inhibitors, [19][20][21][22][23] some with a reduction in IHTG on liver imaging, [21][22][23] while a larger placebo-controlled study with dapagliflozin did not observe an improvement in IHTG despite a reduction in subcutaneous and visceral fat. 24 Taken together, the role of SGLT2 inhibitors on IHTG and glucose metabolism remains unclear.…”
Section: Introductionsupporting
confidence: 78%
“…Tobita et al showed additional improvement in histology in a small, uncontrolled study in patients with biopsy-proven NASH. 20 In contrast, a larger placebo-controlled study in 80 patients with type 2 diabetes and NAFLD was negative. 24 While the reasons for the above discordant results remain unclear, in positive studies a decrease in IHTG has usually correlated with a reduction in BMI, visceral fat, and HbA1c levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation